ANALISIS HUBUNGAN ANTARA IKLIM ORGANISASI, KEPEMIMPINAN DAN DISIPLIN KERJA DENGAN KINERJA PEGAWAI DINAS PERTANIAN TANAMAN PANGAN DAN HORTIKULTURA PROVINSI SUMATERA SELATAN - Kamariah SE.MSi (JURNAL KOMPETITIF, 2015)
Department of agriculture food crops and horticulture, South Sumatra Province is implementing elements of the provincial government in the field of agriculture and food crops and horticulture. Duty is to carry out decentralized authority and duties in the field of dekonsentrasi food crops and horticulture. Problems in the research is to find out whether there is a relationship between the organizational climate, leadership, discipline, and work with the Department of agriculture employee performance of food crops and horticulture of South Sumatra Province. As a result it turns out there is a significant relationship between the organizational climate of 57,20% 57,30%, leadership, work discipline 36,30% . It was suggested to head of Department should improve the performance of employees, given the climate of the Organization, leadership and work discipline has a significant relationship with the performance of the employees of the Department of agriculture food crops and horticulture, South Sumatra Province Keywords    : Organizational Climate, Leadership, The Working Discipline & Performance